Herbal essential oils improve growth, antioxidant response, and gene expression in Nile Tilapia fingerlings - Khalafalaa, Malik; Shehab, Shaimaa M.; Aboraya, Mohamed H.; Amer, Asem A.; Farrag, Foad; Abdelghany, Mohamed F.; Alotaibi, Badriyah S.; Abdelmegeid, Mohamed; Shukry, Mustafa; Elolimy, Ahmed A. (Frontiers in Veterinary Science, 2025)
IntroductionThe increasing global demand for sustainable aquaculture practices has prompted the search for natural and effective alternatives to synthetic feed additives. Herbal essential oils (HEOs) have emerged as promising candidates due to their bioactive properties that support growth, health, and immunity in fish.MethodsThis study evaluated the effects of dietary supplementation with blended HEOs—comprising carvacrol, oregano oil, 1,8-cineole, thymol, α-pinene, β-pinene, limonene, and propylene glycol—on growth performance, hematological indices, antioxidant status, immune response, intestinal morphology, and gene expression in Nile tilapia (Oreochromis niloticus) fingerlings. Over a 72-day trial, fish were fed diets with 0 (control), 30, 60, 120, and 240 mL/kg of HEOs.Results and discussionThe 30 and 60 mL/kg groups showed significantly improved final body weight, weight gain, specific growth rate, and feed conversion ratio (p < 0.05). Hematological parameters increased, while serum cholesterol and triglyceride levels decreased. Enhanced lysozyme activity, phagocytic rate, IgM concentration, and antioxidant enzymes (SOD and CAT) were observed in the 30 and 60 mL/kg groups. Additionally, these doses significantly upregulated the expression of growth- and immunity-related genes (GHr, IGF-I, IL-1β, TNF-α, ZO-1, and occludin) while downregulating HSP70, indicating improved stress resilience. Histological analysis revealed increased villi height and surface area in the intestine, suggesting better nutrient absorption. These findings demonstrate that dietary supplementation with 30–60 mL/kg of HEOs can enhance physiological and immunological health, offering a natural strategy to improve Nile tilapia aquaculture productivity.